Increased incidence of herpes zoster in the setting of cytomegalovirus preemptive therapy after kidney transplantation. Issue 4 (15th May 2013) - Ko, G.B.; Kim, T.; Kim, S.‐H.; Choi, S.‐H.; Kim, Y.S.; Woo, J.H.; Kim, Y.H.; Park, J.B.; Lee, S.K.; Park, S.‐K.; Park, J.S.; Han, D.J.; et al.
Abstract Background Herpes zoster (HZ) is a common infectious disease after kidney transplantation (KT). The incidence of HZ may increase during cytomegalovirus (CMV) preemptive therapy. We therefore evaluated the incidence, risk factors, and clinical outcomes of HZ after KT, according to the type of CMV prophylaxis used. Methods We retrospectively established a cohort of KT recipients who underwent transplantation from June 2008 to May 2010. Patients were categorized into 3 groups according to CMV prophylaxis regimen: Group A (preemptive therapy), Group B (universal prophylaxis <3 months), and Group C (universal prophylaxis >3 months). The incidence rate of HZ was compared in each group, and risk factors for HZ were identified. Results The incidence rate of HZ was 46.6 (95% confidence interval [CI] 31.4–66.5) per 1000 person‐years. The incidence rate was higher in Group A than in Group C (80.0 vs. 13.0 per 1000 person‐years; P = 0.001). Median onset time of HZ after KT was shorter in Group A than in Group B (0.9 vs. 9.9 months; P < 0.001) and Group C (0.9 vs. 14.8 months; P = 0.008). Post‐herpetic neuralgia occurred in 7 patients (23%). No visceral involvement or death was related to HZ. By multivariate analysis, only female gender (corrected relative risk 1.59; 95% CI 1.09–2.00) was independently associated with HZ development. Conclusions In the setting of CMV preemptive therapy, a differentiated varicella zoster virus‐specific prophylaxis might be necessary for patients with HZ risk factors.